Sharps injuries among health care workers in Al Ahsa region, Saudi Arabia - Al Shaikh, Hanan Ahmed; Al Mahdi, Maher Mohammad; Naik, Balaji Rama (International Journal of Infection Control, 2019)
Data on needle stick injuries and other sharps injuries were collected and analysed for a period of three years from 2016 to 2018 to see the probable risk factors including, for example, type of device, location of injuries, work site, and job category. Nurses were found to be more prone for injuries, with hollow bore needles reported as the most common device involved. Housekeepers formed a major portion of staff with reported injuries and with source unknown. There are gaps in collecting data and quality of data. Focused training for high risk categories, with customized materials suitable to the staff, are recommended to prevent the injuries.Keywords:Sharps, Needle stick injuries, NSIs, HCWs, Housekeepers